2015
DOI: 10.1016/j.bmc.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antiangiogenesis evaluation and molecular docking studies of 1-aryl-3-[(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas: Discovery of a new substitution pattern for type II VEGFR-2 Tyr kinase inhibitors

Abstract: The synthesis and biological evaluation of novel 1-aryl-3-[2-, 3- or 4-(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas 3, 4 and 5 as VEGFR-2 tyrosine kinase inhibitors, are reported. The 1-aryl-3-[3-(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas 4a-4h, with the arylurea in the meta position to the thioether, showed the lowest IC₅₀ values in enzymatic assays (10-206 nM), the most potent compounds 4d-4h (IC₅₀ 10-28 nM) bearing hydrophobic groups (Me, F, CF₃ and Cl) in the terminal phenyl ring. A convincing rationalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(63 citation statements)
references
References 20 publications
3
60
0
Order By: Relevance
“…Altogether, our findings indicate that since these compounds also inhibit some angiogenic steps in endothelial cells [Machado et al, 2015] and in the present study consistently showed anticancer effects at very low concentrations in breast cancer cell lines, particularly in MDA-MB-231 cells, these molecules may have wide therapeutic and/or adjuvant application in the treatment of the most aggressive TNBC. Compounds 1c (R 2 ¼ Me) and 1e (R 1 ¼ Cl, R 2 ¼ CF 3 ) were the most promising compounds, being thus considered for further studies.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Altogether, our findings indicate that since these compounds also inhibit some angiogenic steps in endothelial cells [Machado et al, 2015] and in the present study consistently showed anticancer effects at very low concentrations in breast cancer cell lines, particularly in MDA-MB-231 cells, these molecules may have wide therapeutic and/or adjuvant application in the treatment of the most aggressive TNBC. Compounds 1c (R 2 ¼ Me) and 1e (R 1 ¼ Cl, R 2 ¼ CF 3 ) were the most promising compounds, being thus considered for further studies.…”
Section: Discussionsupporting
confidence: 81%
“…Our previous studies were focused on the inhibitory effects of new 1-aryl-3- [3-(thieno[3,2-b]pyridin-7-ylthio)phenyl]ureas on several steps of angiogenesis, targeting VEGFR-2 tyrosine kinase activity [Machado et al, 2015]. The fact that cancer cells generally overexpress receptors with tyrosine kinase activity (similar to VEGFR-2), led us to investigate whether these compounds also affected breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II inhibitors induce the inactive DFG‐out conformation of the activation loop, enabling them to occupy the hinge region and an adjacent allosteric site. Hydrogen bond interactions between inhibitors and RTKs afford a common binding conformation for design of inhibitors …”
Section: Multiple Rtkis As Antiangiogenic Agentsmentioning
confidence: 99%
“…Hydrogen bond interactions between inhibitors and RTKs afford a common binding conformation for design of inhibitors. 194 The three types of RTKIs share a basic architecture for construction, which can be defined by four key interactions:…”
Section: Structural Analysis Of Multitarget Inhibitorsmentioning
confidence: 99%